Students' knowledge and perception of functions and management of trees in the trees in the University of Ibadan (2012)
This study assessed the perception and level of information about trees possessed by the students in the University of Ibadan in order for the trees’ managers to develop appropriate management strategy for sustainable production of the trees’ service functions for the optimal and continuous benefits of the students. A two-stage stratified random sampling procedure was used to administer questionnaire on 315 respondents drawn from all the halls of residence (11) and faculties (10) in University of Ibadan. Hence, 165 respondents were randomly selected from the 11 halls of residence, while 150 respondents were randomly selected from the 10 faculties, making a total of 315 respondents.The data collected were analysed with descriptive statistics and Chi-square (χ2) at p = 0.05. Most (90.6% and 95.2%) were aware of presence of trees around their classrooms and halls of residence respectively. Students’ awareness of presence of trees around classrooms is not dependent on the faculty of the students while awareness of presence of trees around halls of residence is dependent on the halls of residence of the students. Cooling the environment ranked highest (31.3%) among the identified functions, while provision of shade ranked highest (30.1%) among the benefits derived from the campus trees. Although 68.2% iterated that trees do not pose danger on the campus, 82.8% identified falling down of trees during windstorm and falling of old weak trees as major threatsby trees, while 56.7% identified old age of trees as a major reason for tree hazards. Furthermore, 72.9% was of the opinion that the trees on the campus should not be removed, 95.4% was of the view that trees are necessary within the premises of the campus; 90.9% opined that more trees should be planted in the university; 94.2% agreed that trees beautify and make the environment attractive; 90.9% indicated that trees purify the air we breathe; 89.0% was of the opinion that trees in the University premises make the environment to be serene while 74.1% consented that presence of trees marks the university premises out from the surrounding environment. Moreover, 92.6% believed that proper management of trees in the University can reduce hazards associated with the trees, 74.7% was at variance with the statement that trees in the University campus are too many and should be reduced, 80.7% concurred with the statement that old trees within the premises should be replaced by newly planted ones, 77.5% acceded that asides replacing old ones, more trees should also be planted on the University campus. Moreover, 75.5% subscribed to forestry education not being limited to the Department of Forest Resources Management while 77.5% saw the need for awareness campaign for planting of trees on the campus. The Campus Tree Management Committee will have to expedite actions towards mitigation of tree hazards and have to be more feasible, proactive and creative in developing sustainable greenery for the University environment. Also the Department of Forest Resources Management course on Introduction to Forestry (FRM 210) and that of the Faculty of Agriculture and Forestry General Study course (GES 105) will have to be reviewed to incorporate a chapter each on the fundamentals of Arboriculture.